Q-deformed fermionic Lipkin model at finite temperature - Galetti, D. [UNESP]; Pimentel, B. M. [UNESP]; Lima, C. L.; Lunardi, J. T. (Elsevier, 1997)
The interplay between temperature and q-deformation in the phase transition properties of many-body systems is studied in the particular framework of the collective q-deformed fermionic Lipkin model. It is shown that in phase transitions occuring in many-fermion systems described by su(2)q-like models are strongly influenced by the q-deformation.
Keywords: Many-fermion systems; Phase transition; q-algebras; Algebra; Mathematical models; Fermionic Lipkin model; Many fermion systems; Phase transitions